ANALISIS PENGARUH 7 DAY RATE REPO, INFLASI, NILAI TUKAR, DAN PDB TERHADAP INDEKS HARGA SAHAM SEKTOR PROPERTI (STUDI EMPIRIS DI BURSA EFEK INDONESIA) - Wiyanti, Rahma (JAK (Jurnal Akuntansi) : Kajian Ilmiah Akuntansi, 2018)
Since the introduction of the new 7-day Repo rate formula in 2016, it will be a signal forinvestors, especially the property sector to invest in capital markets. Enforcement isencouraging the property sector to grow because it is expected the new interest rate formulawith a value lower than before can attract consumers to invest in property. With thewidespread demand for property pushed the performance of property entrepreneurs tobecome better in the financial sector. The development of property performance is seen fromthe Stock Price Index in the property sector. Researchers test whether the formula along withother macro variables such as Inflation, Exchange Rate and GDP can affect the valuation ofinvestors in investment in the capital market, especially in the property sector. Analysis testthat has been done by using statistical method of Multiple Linear Regression Test,Correlation Coefficient Test, Determination Coefficient Test, F Test and T Test resulted in 7Days Rate Ratio and exchange rate significantly affect Stock Price Index in property sectorwhile Inflation and GDP did not influence Stock Price Index of property sector, butsimultaneously produce variable 7 Day Rate Repo, Inflation, exchange rate and GDP effecton Stock Price Index in property sector.